DETERMINATION OF WATER RETENTION BY THE NATIVE FIELD OF THE PAMPA BIOME WITH SIMULATED RAIN - JAEGER, CABRIELI ALINE; SPOHR, RENATO BEPPLER; BAUMHARDT, EDNER; RONTANI, FAGNER AUGUSTO (Ra’e Ga: o Espaço Geográfico em Análise, 2024)
Pampa was one of the most neglected biomes in Brazil, mainly due to its floristic composition distinct from the others. The expansion of agriculture and forestry are often linked to the advancement of negative impacts on the hydrology of this biome. However, there isn’t enough information about the hydrological functioning of small basins with native vegetation in Pampa. The objective of this study is to evaluate the applicability of two different methodologies to determine water retention by native vegetation of the Pampa Biome, using a rainfall simulator. The methodology 1 used structured samples of native field vegetation and soil, and methodology 2 used only vegetation samples without the presence of soil; all of which were submitted to the application of simulated rain. With the obtained data, the amount of water that this vegetation retains during rainy events was estimated. Using method 1, we found estimated retention values of 5.4% and 10.9%, 18.6% and 27.8%. However, through method 2 we found estimated retention values of 8.5% and 12.7%. In any case, both methods showed significant values of water retention by this vegetation, being the variations found associated with the methodology itself, or the natural characteristics of each study area.